IoT climate resilience in Central Asia: understanding perceived risks through a user survey analysis applied to Kazakhstan - Zhunissova, Dinara; Topping, David; Evans, James (Frontiers in Sustainable Cities, 2025)
Climate change poses significant risks to the resilience of Internet of Things (IoT) infrastructure, especially in regions with extreme and variable climates such as Central Asia. Despite the rapid adoption of IoT technologies across sectors, limited attention has been given to how these devices perform under climate change. This study addresses this gap by analysing the results of an online survey of 150 stakeholders from public and private sector organisations in Kazakhstan, representing transportation, logistics, meteorology, ecology, and IT. The survey assessed organisational dependency on various IoT devices, perceived impacts of weather, maintenance practices, protective measures, and access to environmental performance data. The findings show that sensors, SIM cards, and outdoor routers are the most operationally critical, with sensors identified as the most climate-sensitive, requiring monthly or yearly maintenance and additional housing protection. In contrast, outdoor routers and actuators showed relatively higher resilience. Over half of respondents reported moderate climate change risk to operations, but a substantial information gap remains, with many organisations lacking vendor-provided performance data for extreme conditions. This lack of transparency limits informed procurement, risk assessment, and resilience planning. The study contributes one of the first regional assessments linking IoT operational risks to climate variability in Central Asia and provides actionable recommendations for integrating resilience into procurement standards, establishing open performance data repositories, and developing sector-specific adaptation strategies.